2020
DOI: 10.1530/ec-20-0342
|View full text |Cite
|
Sign up to set email alerts
|

Management of endocrine immune-related adverse events of immune checkpoint inhibitors: an updated review

Abstract: Immune checkpoint inhibitors (ICIs) belong to a new group of anticancer drugs targeting T-cell proteins involved in the activation of immune response toward malignancies. Their introduction into clinical practice was a milestone in modern cancer treatment. However, the significant advantage of ICIs over conventional chemotherapy in terms of therapeutic efficacy is accompanied by new challenges related to specific side effects. ICI-induced immune system activation could lead to the loss of self-tolerance, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(152 citation statements)
references
References 142 publications
(300 reference statements)
3
142
0
7
Order By: Relevance
“…Additional important aspect is to decide whether thyroid hormone replacement is to be maintained after stopping PD-1/PD-L1 inhibitor therapy. Current guidelines recommend to maintain thyroid hormone replacement during PD-1/PD-L1 inhibitor therapy and consider cessation of thyroid hormone replacement by re-measurement of thyroid function status after complete interruption of the therapy [ 3 , 29 ]. In the present study, most patients (11/13, 84.6%) who stopped PD-1/PD-L1 inhibitor therapy required same doses of levothyroxine, while two patients required reduced doses of levothyroxine during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Additional important aspect is to decide whether thyroid hormone replacement is to be maintained after stopping PD-1/PD-L1 inhibitor therapy. Current guidelines recommend to maintain thyroid hormone replacement during PD-1/PD-L1 inhibitor therapy and consider cessation of thyroid hormone replacement by re-measurement of thyroid function status after complete interruption of the therapy [ 3 , 29 ]. In the present study, most patients (11/13, 84.6%) who stopped PD-1/PD-L1 inhibitor therapy required same doses of levothyroxine, while two patients required reduced doses of levothyroxine during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Transient thyroiditis was diagnosed as noticeable hyperthyroidism or subclinical hyperthyroidism at the time of diagnosis and subsequently progressing to hypothyroidism ( 22 ). The latest review and meta-analyze have reported high thyroid IRAEs frequencies, especially relatively high risk for hypothyroidism ( 42 ). Notably, ICIs-related thyroid dysfunction incidences lie on the type of malignant tumor and ICIs employed ( Table 1 ).…”
Section: Specific Effects Of Iraes On the Thyroidmentioning
confidence: 99%
“…Stelmachowska-Banas et al. ( 42 ) summarized that combination therapy has been associated with the highest estimated incidence of high thyroid dysfunction frequencies, ranging from 8.0 to 16.4%, remarkably higher than monotherapy with anti-PD-1 drugs (2.8-8.5%) or anti-PD-L1 drugs (0.6-6.0%) or anti-CTLA-4 (0.2-5.2%). The combination of multiple immunotherapies can increase the risk of thyroid dysfunction ( 23 , 43 46 ).…”
Section: Specific Effects Of Iraes On the Thyroidmentioning
confidence: 99%
See 2 more Smart Citations